AVALIAÇÃO DAS ALTERAÇÕES NO ESMALTE APÓS APLICAÇÃO DE UM AGENTE CLAREADOR E ESCOVAÇÃO COM DENTIFRÍCIOS CLAREADORES - Hilgenberg, Sérgio Paulo (2008)
The aim of this study was to evaluate the physical-chemical and microbiology characteristics of 3 whitening toothpastes: Close-up Whitening - G1; Sorriso Branqueador - G2; Sensodyne Branqueador - G3, as well as, the action of the same ones on the dental enamel, when used alone or, after to the application of 16 carbamide peroxide. Firstly, they took place the physical-chemical and microbiologic analyses. Test chemical: Analysis of the pH: was dispersed 5g of toothpaste in 15mL of distilled water, after 24 hours the solution was analyzed in pHmeter. Physical tests: 1 – residue analysis: it was weighed 5g of toothpaste, submitted to the heating (105C/24h) and appraised the mass, after constant weight. 2 - Tenor of ashes: 2g of toothpaste were roasted (500C/30min). 3 - Analysis in MEV and EDX of the ashes. Test microbiologic: was used the kit Newplus, usually employed for microbiologic control of cosmetics. For the evaluation of the effect on the roughness of the enamel, were made 30 specimens, with three enamel segments (4 x 4 mm), obtained using a diamond disk. A perfilometer was used to determine the values of roughness average (Ra), total roughness (Rt) and Ry, initials and after the application of the bleaching agent and brushing with whitening toothpastes. The bleaching was accomplished in the surface of the fragments by 10 hours, and the brushing was accomplished in brushing machine. It was applied in one of the segments, after the bleaching agent, topical fluoride. Significant differences was found in the physiochemical parameters (p <0.05 - ANOVA, pos-test of Bonferroni). pH Test: G1=7.9±0.1; G2=10.1±0.1 and G3=9.1±0.1. Residue analysis: G1=44.7±1.1, G2=65.8±2.2 and G3=39.9±1.1. Tenor of ashes: G1=17.6±1.2, G2=36.6±2.0 and G3=16.0±3.1. The EDX test found chemical elements indicated by manufacturers in the formulation. The SEM demonstrated differences in the morphology of the abrasives. The microbiological test no detected bacterial or fungus contamination. The data initials and final of the three roughness parameters (Ra, Rt and Ry) were submitted to the t-Student test, that demonstrated there to be differences among the applied treatments to the enamel and the interaction with the toothpaste: for G1 - all of the roughness parameters were altered when the brushing was preceded of bleaching agent and, for G2, the use of the toothpaste on the enamel, altered the parameter of roughness average. It was concluded that differences exist in the physical-chemical properties of the tested toothpastes (solid residue, tenor of ashes and pH) taking to different abrasive potential and possibly to different therapeutic functions; there was not microbial contamination in any analyzed toothpaste, demonstrating a good quality control in the production of the same ones; differences exist in the morphology and composition in the abrasive agents of the studied toothpastes, taking to different abrasive potential; the parameter of roughness average was just altered for when Sorriso Branqueador was used on the dental enamel; the use of bleaching agent previously to the brushing with abrasive toothpaste was factor that determined alteration in the three roughness parameters for the group Close-up Whitening and, use of topical fluoride for one minute after the exhibition to bleaching agents went effective to avoid alteration in the roughness parameters in the group Close-up Whitening.